Decolonizing global cultures: searching for cultural identity through the Chinese orchestra in Malaysia - Tan, Elynn (2020)
The history of the modernized Chinese orchestra dates back to the 1919 New Cultural Movement in China, revolutionized by the state from pre-existing traditional Chinese music. It is then spread to other regions with significant Chinese population sizes, including diasporic Chinese communities such as Malaysia. Literature on the Chinese orchestra in Malaysia is limited to mostly historical studies of particular orchestras. Hence, this research adds on to the field of study by examining the Malaysian Chinese orchestra from another perspective using William’s theory on hegemony and Hall’s concept of diasporic identity. With a focus on deconstructing the cultural identity of the Malaysian Chinese diaspora, the Chinese orchestra is examined from its origins and development in China that has political foundations related to China’s modernizing and Westernizing policies. Additionally, processes of becoming of the Chinese orchestra in regions like Taiwan, Hong Kong, Singapore, and Malaysia are briefly discussed for a better understanding of hegemonic structures and their effect on the dissemination of cultural products, especially since cultural identity is reconstructed and transformed over space and time. In negotiations of a heterogenous identity, the minority position of the Malaysian Chinese diaspora opens creative space for the hybridization of Chinese orchestra music, to develop transcultural and transboundary music in its own trajectory that relates to its rootedness to motherland cultures and its current social context. The comprehension of transculturation from the Malaysian Chinese viewpoint is a strategy to decolonise heterogenous cultures for the recognition of differences from multiple angles.